أثر الاستثمار في التحول الرقميعلى هيكل تمويل الشركات الصناعية (مجلة جامعة دمشق للعلوم الاقتصادية و السياسية, 2025)
The study aimed to examine the role played by the expansion of investment in digital transformation on the financing structure of industrial companies, as the cost of data collection, storage, and processing reduced as the Internet and new technologies developed. By introducing automation systems and technology in all fields, the pace of operations was accelerated and technology improved.As part of the study, two listed industrial companies of stock Damascus exchange (Al-Ahliah and Al Badia) published financial statements were examined, based on those financial ratios, we calculated the necessary study indicators and conducted a simple linear regression study based on mathematical calculations for the financing structure of these companies. According to the study model, multivariate analyses were performed on the dependent and independent variables of the study, and variances in differences were tested.The study found that investments in digital transformation affected the financing structure of industrial companies by affecting the proportion of long-term assets covered by invested capital, as well as short-term financing. It does not appear that investment in digital transformation has a statistically significant impact on industrial companies' external financing ratio and long-term debt coverage ratio, which are indicators of full indebtedness. Study findings also indicate a relationship between digital transformation investments and industrial company financing structures.